Digital Practicum Module in Integrated Science for Elementary School Subjects - Ni Luh Putu Suci Utami Putri; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2023)
The low use of practicum modules in the Integrated Elementary Science learning process. This study aims to create a digital practicum module in Integrated Elementary Science courses. This type of research is research and development with the ADDIE stage process. The subject of this research is the validity of the content, design, and media of the practicum module and the practicality of the practicum module. Data collection methods are literature study methods, questionnaires, and interviews. The instrument form is a rating scale with descriptive, qualitative, and quantitative data analysis techniques. The results showed that this study successfully produced a digital practicum module in the Integrated Elementary Science course in Elementary School Teacher Education. The level of achievement of media validity is 94%, content validity is 94%, and design validity is 92.5%. It shows that the validity reaches a very good predicate. The level of achievement of the practitioner's response obtained a value of 94% with a very good predicate; The level of achievement of the media practicality response in the individual test obtained a value of 98.33%; And the level of achievement of the practitioner's response in the small group test obtained a value of 97.5% with a very good predicate. The conclusion shows that the developed product as a digital practicum module in Integrated Elementary Science courses can be declared valid, practical, and feasible for learning. This study implies that there is a digital practicum module that can support the learning process of Integrated Elementary Science.